Kalmykia in Russia's past and present national policies and administrative system - Maksimov, K. N. (Konstantin Nikolaevich) (Central European University Press, 2008)
Kalmykia is a constituent of the Russian Federation that shaped and has been developing within Russia for several centuries. Kalmykia was incorporated into the Russian state in the early second half of the 17 th century, it was officially recognized by the Russian authorities and constituted as an ethno-political entity in the form of feudal khanate with the status of a virtually autonomous unit. The Kalmyk Khanate's status as a largely self-ruling area within the Russian Empire gradually transformed into the status of a regular administrative territory under the Astrakhan governor. It received the status of a Republic from Stalin.Maksimov examines issues of interrelations between the Kalmyk people and Russia before and after the Kalmyks' accession to the Russian state. Analyzes the Soviet national policy and to the destiny of Kalmykia under the communist regime. The legal status of this republic and its development under the new Russian federalism are discussed in great details.